Hubungan Usia, Pengetahuan Ibu dan Dukungan Suami dengan Pemberian Imunisasi Campak Pada Bayi Usia 9 Bulan di Wilayah Kerja Puskesmas 23 Ilir Palembang Tahun 2021 - Timur Yadi; Yazika Rimbawati; Fitri Afdhal (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Measles immunization is an immunization given to generate active immunity against measles. (Maryunani, 2010). Immunization is a health effort that has been proven to be the most effective. When immunization coverage reaches 90%, it can contribute to reducing morbidity and mortality by 80% - 90%. Although measles immunization coverage has been high (90%) but there are still children affected by measles. Because the remaining 10 percent of children who have not received immunizations plus 10 percent of children who are immunized but are not immune cause people's immunity to only reach 81%. (Center for public communication of the Indonesian Ministry of Health, 2015). The purpose of this study was to determine the relationship between age, mother's knowledge and husband's support simultaneously with the provision of Measles Immunization to infants aged 6-9 months in the Work Area of 23 Ilir Palembang Health Center in 2021. This design is quantitative in nature using an analytical survey method where the research This study uses a cross sectional approach. This research was conducted in the working area of 23 Ilir Health Center, Palembang with 83 respondents. And the results of the Chi-Square test on the knowledge variable obtained a p value of 0.038, age variable p.value 0.003 and variable p.value 0.001 < = 0.05 there is a relationship between the variables of knowledge, age and husband's support with measles immunization. statistically. Suggestions for health workers Conduct socialization to the community to take advantage of government programs by giving their children measles immunization according to the specified schedule, and if they know their child has measles, it is necessary to isolate the case to prevent transmission of measles.